(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper probes into the employment of spatial theory in the works of Mark Twain, an eminent American author celebrated for his astute commentary on society. Spatial theory, rooted in geography and cultural studies, provides a lens through which one can analyse the ways in which Twain’s literary landscapes echo and assess societal constructs. By examining the spatial scopes within Twain’s works, this paper aims to shed light on how the author circumnavigates and challenges prevailing norms, ideologies, and power structures.